2004
DOI: 10.1107/s160053680400008x
|View full text |Cite
|
Sign up to set email alerts
|

An orthorhombic polymorph ofN,N′-bis(2-pyridylmethyl)pyrazine-2,3-dicarboxamide

Abstract: Key indicatorsSingle-crystal X-ray study T = 153 K Mean '(C±C) = 0.002 A Ê R factor = 0.032 wR factor = 0.079 Data-to-parameter ratio = 10.1For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Hausmann et al (2003) also reported the structure of a dimeric Cu(BF 4 ) 2 complex with the ligand in a zwitterion form and coordinating in an unusual tridentate(N 3 )±monodentate(O) fashion. A similar complex with Cu(NO 3 ) 2 has been observed by Cati & Stoeckli-Evans (2004b). The structure of a mononuclear cobalt(III) complex with the ligand in a zwitterion form, coordinating in a tridentate fashion, has also been reported (Cati & Stoeckli-Evans, 2004c).…”
Section: Commentsupporting
confidence: 57%
See 1 more Smart Citation
“…Hausmann et al (2003) also reported the structure of a dimeric Cu(BF 4 ) 2 complex with the ligand in a zwitterion form and coordinating in an unusual tridentate(N 3 )±monodentate(O) fashion. A similar complex with Cu(NO 3 ) 2 has been observed by Cati & Stoeckli-Evans (2004b). The structure of a mononuclear cobalt(III) complex with the ligand in a zwitterion form, coordinating in a tridentate fashion, has also been reported (Cati & Stoeckli-Evans, 2004c).…”
Section: Commentsupporting
confidence: 57%
“…Cati et al (2004) also described the synthesis of H 2 L and the structure of its triclinic polymorph. The structure of the orthorhombic polymorph of H 2 L has also been described recently (Cati & Stoeckli-Evans, 2004a). Hausmann et al (2003) also reported the structure of a dimeric Cu(BF 4 ) 2 complex with the ligand in a zwitterion form and coordinating in an unusual tridentate(N 3 )±monodentate(O) fashion.…”
Section: Commentmentioning
confidence: 82%
“…The title ligand, N 2 ,N 3 -bis(quinolin-8-yl)pyrazine-2,3-dicarboxamide (H 2 L1), is very similar to ligand N 2 -[(2,3-dihydropyridin-2-yl)methyl]-N 3 -(pyridin-2-ylmethyl)pyrazine-2,3-dicarboxamide (H 2 L2), for which two polymorphs have been reported Cati & Stoeckli-Evans, 2004). These and other pyrazine-carboxamide ligands were synthesized to explore their coordination behaviour with first-row transition metals and to study the magnetic exchange behaviour of the complexes (Cati, 2002).…”
Section: Chemical Contextmentioning
confidence: 97%
“…Binuclear copper(II) complexes with the ligand coordinating in the bis-tridentate coordination mode (HL À ) have been observed (Cati et al, 2004;Cati & Stoeckli-Evans (2004b). Structures of both copper(II) (Hausmann et al, 2003;Cati et al, 2004) and nickel(II) (Cati et al, 2004) [2 Â 2] grid complexes have been described with the ligand coordinating in a bis-tridentate manner as HL À .…”
mentioning
confidence: 99%